MENGULIK KETANGGUHAN (HARDINESS) PEDAGANG UMKM DI TENGAH MARAKNYA E-COMMERCE - Wibowo, Wasis Purwo (Faculty of Ushuluddin and Humanities, 2024)
Current technological advances have a significant impact. All conveniences can be obtained with this progress, including in the business of buying and selling goods. On the other hand, advances in digitalization have made businesses look empty due to the decline in consumers shopping in person. The aim of this research is to explore the toughness of MSME traders around the Suramadu bridge on the Madura side. The method used is descriptive-qualitative. The informant criteria used were two small and medium-sized traders around the Suramadu bridge on the Madura side. The results of the analysis show that MSME traders around the Suramadu Bridge on the Madura side have good resilience amidst the rise of e-commerce. All existing aspects, namely control, commitment, and challenge, are classified as good and show toughness and tenacity in carrying out their activities. Keywords: Hardiness, E-commerce, UMKM Traders